Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.brs.2020.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Neural selectivity, efficiency, and dose equivalence in deep brain stimulation through pulse width tuning and segmented electrodes

Abstract: Background: Achieving deep brain stimulation (DBS) dose equivalence is challenging, especially with pulse width tuning and directional contacts. Further, the precise effects of pulse width tuning are unknown, and recent reports of the effects of pulse width tuning on neural selectivity are at odds with classic biophysical studies. Methods: We created multicompartment neuron models for two axon diameters and used finite element modeling to determine extracellular influence from standard and segmented electrodes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 43 publications
2
58
1
1
Order By: Relevance
“…We modeled as previously described using the finite element method (FEM) 1,2 , implemented in SCIRun 5.0 (Scientific Computing and Imaging (SCI), Institute, University of Utah, Salt Lake City, UT), to solve the bioelectric field problem. We set electrode contacts as ideal conductors and electrode shafts as ideal insulators.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We modeled as previously described using the finite element method (FEM) 1,2 , implemented in SCIRun 5.0 (Scientific Computing and Imaging (SCI), Institute, University of Utah, Salt Lake City, UT), to solve the bioelectric field problem. We set electrode contacts as ideal conductors and electrode shafts as ideal insulators.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, we repeated experiments with different conductivities, including and excluding an encapsulation layer and found that while activation thresholds changed in response to changes in conductivity layer, the conclusions were similar regardless of conditions. We implemented a Dirichlet boundary condition at the outer edge of the model to serve as a distant ground 1,8,18 (100 mm x 100 mm x 100 mm) and solved for the electric potential solution.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations